2017
DOI: 10.1177/0218492317717421
|View full text |Cite
|
Sign up to set email alerts
|

Pneumorachis associated with persistent tachycardia after blunt thoracic trauma

Abstract: Pneumorachis, or intraspinal air, can be a rare result of blunt thoracic trauma. We report the case of a 40-year-old man with multiple injuries and pneumorachis associated with persistent tachycardia. As factors that increase heart rate were gradually ruled out, intraspinal air was considered the potential culprit. Computed tomography revealed intraspinal air at the thoracic level, which possibly promoted cardiac arrhythmogenesis. Air may transiently compress the preganglionic cardiac sympathetic nerves and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…As is known, cardiac lesions that may develop in patients after blunt thoracic trauma can vary in a wide spectrum ranging from an uncomplicated myocardial contusion to major vessel injuries (3,11). It is known that arrhythmias may occur following cardiac injuries that may develop after trauma (12). Our study showed that Tp-e interval, Tp-e/QT ratio, and Tp-e/QTc ratio could indicate an early diagnosis of arrhythmia that may develop after blunt chest trauma.…”
Section: Discussionmentioning
confidence: 53%
“…As is known, cardiac lesions that may develop in patients after blunt thoracic trauma can vary in a wide spectrum ranging from an uncomplicated myocardial contusion to major vessel injuries (3,11). It is known that arrhythmias may occur following cardiac injuries that may develop after trauma (12). Our study showed that Tp-e interval, Tp-e/QT ratio, and Tp-e/QTc ratio could indicate an early diagnosis of arrhythmia that may develop after blunt chest trauma.…”
Section: Discussionmentioning
confidence: 53%
“…Pneumorrachis had several definitions (pneumocele, pneumatosis, emphysema, aerorachia, pneumosaccus, air myelogram) before Gordon and Hardman (1977) describe the fixed term "pneumorrachis".1 About less than 80 case reports have been published worldwide, while many articles are not available online and not all were caused by traumatic pneumothorax (Table 1). 1,3,[7][8][9][10][11][12][13][14][15][16][17][18][19] Pneumorrachis can be classified into internal and external. The internal pneumorachis is defined as the finding of air in the intradural space (subdural or subarachnoid), while the external pneumorachis is defined as the finding of air in the extradural space (intraspinal and epidural).…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported 6 similar case of pneumorrachis following blunt chest trauma but there is no further explanation about it. 19 There were others 5 cases about pneumorrachis with pneumothorax as its underlying cause, however, no full text was available online. The intraspinal gas has the same low CT scan density with other gases must be clearly differentiated from gas due to infective, degenerative, malignancy, and inflammation.…”
Section: Discussionmentioning
confidence: 99%